Uji Eksperimental Emisi Gas Buang Mesin Bensin 160 cc Berbahan Bakar Campuran Pertalite-Butanol dan Pertalite-Diethyl Ether (DEE) - Firman Lukman Sanjaya; Syarifudin; Faqih Fatkhurrozak; Nur Aidi Ariyanto (P3M Politeknik Negeri Cilacap, 2022)
Air pollution is increasing due to the high exhaust emissions of motorized vehicles using fossil fuels. The solution is the use of alternative energy. Butanol and Diethyl Ether (DEE) are alcohols that can be used as a fuel mixture and are environmentally friendly. This is because butanol and DEE have high oxygen levels so the oxidation process in the combustion chamber increases and the residual gas results from combustion is better. This study tested the residual gas from the combustion of a 160 cc gasoline engine using a mixture of pertalite-butanol and pertalite-DEE fuels with 5%, 10%, and 15% alcohol percentages. The test results show that adding DEE produces better engine exhaust emissions than adding butanol. CO emissions decreased by 87% using DEE15 while B15 reduced CO by 72%. DEE10 improves HC by 73% while B15 improves HC by 72%. However, DEE15 increases CO2 by 17% and B15 by 11%. Meanwhile, the oxygen content increased by 8% in DEE15 and 6% in B15 compared to pure pertalite.